2019
DOI: 10.1016/j.drugalcdep.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of 3,4-methylenedioxypyrovalerone (MDPV) in male and female Sprague-Dawley rats

Abstract: Background: 3,4-methylenedioxypyrovalerone (MDPV) toxicity includes intense neurological and cardiovascular events. We examined MDPV-induced cardiovascular, temperature, and locomotor effects following escalating and repeated MDPV administration in adult male and female Sprague-Dawley rats and compared these effects to cocaine in male rats. Methods: Telemetry devices were surgically implanted to allow continuous measurement of cardiovascular, temperature, and locomotor activity over a 22 h period after dosing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Similar to (+)-amphetamine- and (+)-methamphetamine [ 125 ], cathinone also induced significantly higher increases in motor activity in females than in males, and when administered in combination with caffeine, it significantly elevated body temperature acutely in male but not female rats [ 126 ]. Moreover, the duration and intensity of MDPV-induced cardiovascular effects differ among the sexes, lasting significantly longer and being more potent in male than female rats [ 127 ]. Moreover, MDPV produced comparable conditioned place preferences in male and female rats, but weaker conditioned taste avoidance in females compared to males [ 128 ].…”
Section: Synthetic Cathinonesmentioning
confidence: 99%
“…Similar to (+)-amphetamine- and (+)-methamphetamine [ 125 ], cathinone also induced significantly higher increases in motor activity in females than in males, and when administered in combination with caffeine, it significantly elevated body temperature acutely in male but not female rats [ 126 ]. Moreover, the duration and intensity of MDPV-induced cardiovascular effects differ among the sexes, lasting significantly longer and being more potent in male than female rats [ 127 ]. Moreover, MDPV produced comparable conditioned place preferences in male and female rats, but weaker conditioned taste avoidance in females compared to males [ 128 ].…”
Section: Synthetic Cathinonesmentioning
confidence: 99%
“…These results suggest that the acute effects of MDPV on social play behavior are comparable to the effects of other psychostimulants, which are also abused in social settings, such as amphetamine, methylphenidate, or cocaine, that also exert play-suppressant effects in male rats [14,24,40]. Importantly, sex-dependent differences in the effects of MDPV [54][55][56] and in the structure and intensity of social play behavior [23] have been documented. Therefore, investigating the effects of MDPV on social play behavior in female rats, and the neural mechanisms involved, is an intriguing issue which deserves further investigation.…”
Section: Discussionmentioning
confidence: 69%
“…On this basis, we elected to focus on the cardiovascular effects of these compounds in male rats, although additional studies on opioid reward and analgesia are now underway in female rats. Prior studies in both humans and rodents have shown that females are more resilient to the cardiovascular effects of stimulants than males (Mendelson et al, 1999;Lynch et al, 2008;McClenahan et al, 2019) and neither cardiovascular responses to cocaine nor cocaine pharmacokinetics vary across phases of the menstrual cycle (Mendelson et al, 1999). Although relatively few studies exist on sex differences in the cardiovascular effects of opioids, no sex differences in heart rate responses to acutely administered morphine have been identified (Cruz and Rodríguez-Manzo, 2000).…”
Section: Discussionmentioning
confidence: 99%